NOX4-Dependent Hydrogen Peroxide Overproduction in Human Atrial Fibrillation and HL-1 Atrial Cells: Relationship to Hypertension - Zhang, Jun; Youn, Ji Youn; Kim, Antony; Ramire, Rafael; Gao, Ling; Ngo, Doan; Scovotti, Jennifer; Mahajan, Aman; Cai, Hua L. (Frontiers in Physiology, 2012)
Background/Objectives: Atrial fibrillation (AF) is the most common type of cardiac arrhythmia with patients dying frequently of stroke. In view of the unclear etiologies of AF and a potential role of oxidative stress, the present study examined cardiac ROS production and NADPH oxidase (NOX) expression in AF patients. Methods and Results: Patients with AF were older than those without (58.8±11.7 vs. 47.8±19.2, p=0.047). Whereas total O2·- production (determined by electron spin resonance) was similar in patients with and without AF, H2O2 production was more than doubled in AF patients (149.8±26.28 vs. 66.9±7.14 pmol/mg/min, p=0.0055), which correlated well with a doubling in NOX isoform 4 (NOX4) expression. AF patients with co-existing hypertension had three-fold higher H2O2 production compared to those without (239.0±125.1 vs. 83.6±51.3 pmol/mg/min, p=0.003). Treatment of HL-1 atrial cells with angiotensin II, a known modulator of atrial structural remodeling, resulted in upregulation of NOX4 and H2O2 production, further implicating a potential role of NOX4 in atrial remodeling. Conclusions: Our data represent the first implication that NOX4-derived H2O2 may play an important role in the etiologies of AF. Key words：atrial fibrillation (AF) ■ hydrogen peroxide (H2O2) ■ NADPH oxidase ■ NOX4 ■ hypertension ■ HL-1 cells ■ angiotensin II